Prevalence of UTI Caused by Gram-Negative Bacteria in Type 2DM Cases at Khoums Diabetes Center in Al-khoums, Libya. - Ahmed , Raghdah A; alhaseek , Ayadah m.; M, Tamalli; Abousittash , Hanan B. (Sirte Journal of Medical Sciences, 2025)
Urinary tract infections (UTIs) are more frequent, more severe, and have worse outcomes in individuals with type 2 diabetes mellitus. These infections are also more commonly caused by resistant pathogens. Several factors, including immune system dysfunction, poor metabolic control, and incomplete bladder emptying due to autonomic neuropathy, may contribute to the increased risk of UTIs in these patients. A prospective study was carried out at Khoums Diabetes Center in Al-Khoms, Libya, from December 2022 to February 2023. The study included 170 participants, 140 of whom were diagnosed with type 2 diabetes, while 30 were non-diabetic (control group). Among the 140 urine samples from diabetic patients, 60 samples (42.9%) showed significant bacterial growth, while 80 samples (57.1%) showed no significant growth. When examining the relationship between liquid intake, socio-economic status, and Gram-negative bacterial species, the data was categorized by sex, age, weight, and employment. A higher percentage of females (84%) were affected compared to males (16%). The age group most affected was 46-55 years, comprising 35.5% of cases. Regarding employment, housewives were the most affected group, making up 67.8%, while laborers had the lowest incidence, with 0%. Improving the management of diabetes mellitus, along with the proper use of antibiotics selected based on sensitivity patterns, could help reduce the prevalence of urinary tract infections (UTIs) and prevent renal complications. The results highlighted the rise of highly resistant bacteria to most of the tested antimicrobials, urging physicians to adjust their treatment approaches based on antimicrobial susceptibility findings